Legal Protection of Refugee Children Viewed from the United Nations High Commissioner for Refugees : (Case Study of Human Rights of Children in Palestine) - Wendra, Muhammad; Andri Sutrisno (Reformasi Hukum, 2024)
Refugees, especially refugee children, are a group of people who are particularly vulnerable to human rights violations. Children, who lack the problem-solving skills of adults, are often victims of violence and exploitation due to conflict, war and political issues. Especially refugee children will only become inhumane victims. This research aims to examine the importance of legal protection and fulfillment of human rights for refugee children so that their rights can be protected from various forms of crimes against humanity. This research uses the Normative Juridical research method by analyzing international regulations (protocols) applied by UNHCR in protecting refugee children. The results of this study indicate that legal protection and fulfillment of human rights for refugee children is a priority scale that will support their survival. So that the legal protection and fulfillment of human rights for refugee children is an effort to reduce the risk of refugees to crimes that make it easier for them to take part in it or even become victims of a crime. The recommendation of this research is the need for increased international cooperation to protect the rights of refugee children more effectively.